2016
DOI: 10.1111/trf.13883
|View full text |Cite
|
Sign up to set email alerts
|

Patients' outcome after rescue plerixafor administration for autologous stem cell mobilization: a single‐center retrospective analysis

Abstract: Our data demonstrate that plerixafor is highly effective as rescue measurement after mobilization failure with G-CSF alone and short-term clinical outcome after stem cell transplantation is comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…Another study demostrated that plerixafor in combination with G-CSF is an effective rescue measurement for poor mobilizers. Plerixafor was well tolerated by patients who were used plerixafor for stem cell mobilization [24].…”
Section: Discussionmentioning
confidence: 98%
“…Another study demostrated that plerixafor in combination with G-CSF is an effective rescue measurement for poor mobilizers. Plerixafor was well tolerated by patients who were used plerixafor for stem cell mobilization [24].…”
Section: Discussionmentioning
confidence: 98%
“…The possible effect of the infusion of tumor cells on longterm outcomes should be interpreted with caution, as unfavorable outcomes may simply reflect more aggressive disease as well as factors inherent to tumor cell mobilization. It is important to note that it is very likely that some of the patients in our study would probably not have proceeded to autologous transplantation without plerixafor treatment [16][17][18]. In support of our findings, results from a 5-year, long-term, phase III, follow-up study (not restricted to poor mobilizers) showed that the use of G-CSF + P did not have a negative effect on PFS and OS in patients with MM, with more than half of all patients with MM still alive 5 years following transplantation [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the following article, Spoerl and colleagues used a paired t test to compare the concentrations of circulating CD34+ cells in patients being collected for autologous peripheral blood stem cell transplantation. The patients were judged to be poor mobilizers with granulocyte–colony‐stimulating factor stimulation alone.…”
Section: Examples From the Recent Transfusion Literaturementioning
confidence: 99%